The detection of Anaphes sp. nov. [Hymenoptera : Mymaridae], an egg parasitoid of the carrot weevil in Nova Scotia - Hopper, L.R.E.; Le Blanc, J.-P.R.; Boivin, G. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1996)
The wasps Anaphes victus (Huber) and Anaphes listronoti (Huber) [Hymenoptera : Mymaridae] parasitize 50% of the eggs of carrot weevil, Listronotus oregonensis (Le Conte) [Coleoptera : Curculionidae] in Quebec and in Ontario. Attempts to detect either of these egg parasites from exposed carrot weevil eggs in Nova Scotia were unsuccessful. However, 48 individuals of a new species of parasitic wasp, Anaphes sp. nov. [Hymenoptera : Mymaridae], were detected in carrot (Daucus carota) fields in Nova Scotia, using carrots infested in growth chambers with carrot weevil eggs. Anaphes sp. nov. is distinguishable from the other parasites of the carrot weevil by characteristics of the forewing. Anaphes sp. nov. has a forewing length : width ratio greater than 7 :3 while A. victus and A. listronoti have a forewing length : width ratio of less than 6 : 7.